532 Safety in Pregnancy for Female Surgeons: A Pilot Study. (19th August 2022) - Magill, Hayley; Kazzazi, Fawz; Noton, Toby
Abstract: Aim: With an increasing number of female surgeons, it is important to ensure that the workplace is safe for pregnant women, or appropriate adjustments are made. The aim of this study is to ascertain how knowledgeable female surgeons are about potential risks during pregnancy, adaptations they have made, and to guide the design of a bigger study. Method: A literature search was carried out to identify potential risks to pregnant female surgeons. A survey was created to ascertain women's understanding of key which activities are safe in pregnancy, and adjustments some had made whilst pregnant. Results: 100 women responded to the survey, ranging from SHO to consultant. 40% of respondents had children, whilst 78% of those who did not, hoped to have them someday. Only 44% of all respondents felt that they knew what was safe at work during pregnancy, with the majority being unaware of increased risk of complications such as miscarriage, intrauterine growth restriction, placental abruption and gestational hypertension. Conclusions: There is a lack of knowledge of potential risks amongst female surgeons, and most information acquired comes from personal research. Many female surgeons reported complications during their own pregnancies, and many were unaware of these risks prior to pregnancy. A more detailed study including fertility issues, and variations between subspeciality alongside a detailed literature search could start to provide more detailed guidance for female surgeons.